THE MEDIATION ROLE OF BRAND IMAGE ON THE INFLUENCE OF PRODUCT QUALITY ON INTENTION TO PURCHASE THE SAMSUNG S24 ULTRA SMARTPHONE(Study of Smartphone Users in Denpasar City) - Komang Prasetya Wahyu Nugraha; Putu Saroyini Piartrini (Adisam Publisher, 2024)
Lifestyles and the economy are starting to be driven by mobile applications, making the existence of smartphones increasingly important, causing an increase in demand for various types of communication devices and will result in an increasing number of business actors providing/manufacturing communication equipment, resulting in increased competition in the business world in the telecommunications sector. Samsung is the smartphone most often used in Indonesia. The discovery of a business phenomena was evidenced by a drop in Samsung smartphone product sales and a subsequent absence of consumer buy intents. This research aims to analyze the mediating role of brand image on the influence of product quality on purchase intentions for the Samsung S24 Ultra smartphone in Denpasar City from a Signaling Theory perspective, taking into account brand image. The survey data used was 130 customers using purposive sampling. The results of path, Sobel, and VAF analyzes found that The study found that there was a positive and substantial correlation between product quality and buy intention. Additionally, there was a positive and significant correlation between product quality and brand image, and brand image mediated the effect of product quality on purchase intention. for Samsung S24 Ultra smartphone users in Denpasar City. The results of this research have implications for developing business strategies to pay more attention to product quality and brand image so that they can increase purchasing intentions for the Samsung S24 Ultra smartphone in Denpasar City. It is advised that future studies assess consistency by incorporating price into the conceptual model as a moderator.